2022
DOI: 10.1002/eco.2449
|View full text |Cite
|
Sign up to set email alerts
|

The minnowPhoxinus lumaireul(Leuciscidae) shifts the Adriatic–Black Sea basin divide in the north‐western Dinaric Karst region

Abstract: Karst landscapes are characterized by intermittent and sinking streams. The most common method used to study underground hydrological connections in karst is tracing tests. However, a more biologically oriented approach has been suggested: analysis of the genetic structure of aquatic organisms. Biological tracers can be sought among trogloxenes, that is, surface species that occasionally enter caves and groundwater. One such example is the fish genus Phoxinus, which exhibits high genetic diversity and complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…When introduced to non-native rivers and lakes, Phoxinus species quickly spread and are considered invasive in Scandinavia and Spain [52,79,97], attesting again to the adaptability of the genus to new environments [92]. It is clear that Phoxinus species are generalists with a high migratory potential, confirmed also in previous studies [37,39,98], which detected several occasions of the crossing of the Adriatic-Black Sea divide in Dinaric Karst. Especially in lineages 1a and 1b, the genetic structure points to a recurrent, ongoing contact between surface-isolated water systems that are connected underground, keeping the populations in Hardy-Weinberg equilibrium.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…When introduced to non-native rivers and lakes, Phoxinus species quickly spread and are considered invasive in Scandinavia and Spain [52,79,97], attesting again to the adaptability of the genus to new environments [92]. It is clear that Phoxinus species are generalists with a high migratory potential, confirmed also in previous studies [37,39,98], which detected several occasions of the crossing of the Adriatic-Black Sea divide in Dinaric Karst. Especially in lineages 1a and 1b, the genetic structure points to a recurrent, ongoing contact between surface-isolated water systems that are connected underground, keeping the populations in Hardy-Weinberg equilibrium.…”
Section: Discussionsupporting
confidence: 65%
“…While Leuciscinae in Europe are well represented (>320 species), the closest relatives of Phoxinus are distributed in the Pacific basin [54,106,107]. Morphologically, Phoxinus is, in general, characterized by a low level of phenotypic diversity, in contrast to its high level of genetic diversity [38,98,108], whereas Leuciscinae (including Delminichthys, Phoxinellus and Telestes) are highly phenotypically divergent and taxonomically structured in a complex system that also corresponds to their genetic patterns. Nevertheless, when comparing the distribution ranges with other unrelated taxa spread in the Dinaric Karst, some common patterns emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Our high-quality assembly, indicating augmented levels of standing genetic variation, is a testament to this approach. Previous studies have also indicated abundant levels of genetic variation in the Phoxinus genus (Bogutskaya et al, 2020; Reier et al, 2022), potentially enabling more expeditious responses to environmental changes and even greater potential for adaptation across diverse environments (Lai et al, 2019; Matuszewski et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Our high-quality assembly, indicating increased levels of standing genetic variation, demonstrates the effectiveness of this approach. Previous studies have already indicated abundant levels of genetic variation in the Phoxinus genus (Bogutskaya et al, 2020; Reier et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Among the highlighted problems to be addressed were the high intraspecific phenotypic diversity, which makes it difficult to diagnose morphologically similar species (Bogutskaya et al, 2019), and the insufficient information provided by the currently analysed molecular markers for final species delimitation (Palandači c et al, 2020). Finally, in contrast to most leuciscid fishes, it was found that the distribution of species (and/or mitochondrial [mt] clades) in European Phoxinus does not follow current zoogeographic patterns and drainage boundaries (Palandači c et al, 2015(Palandači c et al, , 2017a(Palandači c et al, , 2020Reier, Bogutskaya, & Palandači c, 2022;Reier, Kruckenhauser et al, 2022).…”
Section: Introductionmentioning
confidence: 99%